GUI code tracing through direct program interaction1. Issue 6 (8th April 2014) - Santos, André L.; Ceccato, Mariano; Li, Zheng; Cordy, James R.
ABSTRACT A significant part of a developer's activity is spent on maintenance tasks, which might involve dealing with unfamiliar code. Especially in these cases, a maintenance task is likely to imply a considerable amount of time locating the relevant source code that needs to be changed, a problem often referred to as feature location. This paper proposes a navigation mechanism for tracing user interface elements of a running program to their representation in the source code. The mechanism realization relies on instrumenting the program in order to enable navigation from user interface elements to locations in the source code. We developed a prototype implementation of the proposed mechanism that implies an acceptable instrumentation overhead, suitable for being used on industrial‐scale programs. We performed a user study and observed that the proposed mechanism enables fast code location and that the time spent to accomplish similar tasks does not change significantly as program size increases. Copyright © 2014 John Wiley & Sons, Ltd.